Restoration of native Mediterranean brown trout Salmo cettii Rafinesque, 1810 (Actinopterygii: Salmonidae) populations using an electric barrier as a mitigation tool. Issue 1 (1st January 2018) - Sabatini, A.; Podda, C.; Frau, G.; Cani, M. V.; Musu, A.; Serra, M.; Palmas, F.
Abstract: This study assessed the effectiveness of a novel conservation strategy for the native brown trout populations in Sardinia (Italy). The conservation measures included: (i) installation of an electric fish barrier; (ii) removal of all the resident introgressed brown trout upstream from the barrier; (iii) restocking of the upstream region with native Sardinian trout genetically characterised; and (iv) estimation of native trout population size with prediction of future growth. Introgressed brown trout were removed using multiple-pass electrofishing methods in a 2-km region upstream from the barrier. In two eradication campaigns, conducted in 2010 and 2012, a total of 1801 trout were captured, comprising a total biomass of 55, 501 g. The capture efficiency analysis showed total capture rates of over 99% were achieved for parr (0+ age cohort), and 100% for adult trout. After the eradication campaigns we restocked this area with native brown trout (Adriatic lineage, AD, according to the mitochondrial DNA control region nomenclature). The monitoring campaigns showed good survival (S = 60%) and reproduction of 3.1 recruits/adult trout. Successful breeding was recorded starting from the summer of 2015 and a self-sustaining population resulted after only two restocking events. The results of this restoration project allow recommendations to be made for future conservation eradication and repopulation projects for restoration of typical Mediterranean streams.